Mechanical Behavior and Microstructure Evolution of a Rolled Magnesium Alloy AZ31B Under Low Stress Triaxiality. Issue 12 (December 2016) - Pan, Hongchen; Wang, Fenghua; Jin, Li; Feng, Miaolin; Dong, Jie
Abstract : Plastic deformation up to final rupture failure of a rolled magnesium (Mg) alloy Mg–3.0Al–1.0Zn–0.34Mn (AZ31B) under low stress triaxiality was investigated. Local strain evolution was quantified by the digital image correlation (DIC) technique analysis with tensile, combined tensile-shear, and shear specimens, corresponding to the stress triaxiality of 1/3, 1/6 and 0, respectively. Stress–strain curves show that the yield stress reduces with the decrease in the stress triaxiality, and obviously exhibits different strain hardening response. Electron backscatter diffraction (EBSD) observations reveal that the twinning behavior depends on stress triaxiality. Before fracture, double twinning is the dominant mechanism at the stress triaxiality of 1/3, while extension twinning is prevalent at the stress triaxiality of 0. Moreover, scanning electron microscopy (SEM) shows that the fracture mechanism is transformed from micro-void growth and coalescence to internal void shearing as the stress triaxiality decreases from 1/3 to 0.